1996
DOI: 10.1038/bjc.1996.162
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tropomyosin isoforms in benign and malignant human breast lesions

Abstract: Summary High molecular weight tropomyosins (tms) are commonly down-regulated in fibroblasts transformed by oncogenes. Previous studies have also demonstrated that specific tm isoforms are downregulated in human breast carcinoma cell lines. We examined tropomyosin isoforms in cells prepared from noncancerous breast lesions and primary human breast carcinomas. The average level of expression of all three high molecular weight tm isoforms (tm 1-3) in carcinomas was generally found to be less than 25% of that obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 12 publications
7
60
1
Order By: Relevance
“…Tropomyosin levels were lower in carcinomas than in nonmalignant cells, confirming our previous findings (Franzen et al, 1996). In the material analysed here, the decreases in tropomyosin 2 and 3 were statistically significant, but not that of tropomyosin 1.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Tropomyosin levels were lower in carcinomas than in nonmalignant cells, confirming our previous findings (Franzen et al, 1996). In the material analysed here, the decreases in tropomyosin 2 and 3 were statistically significant, but not that of tropomyosin 1.…”
Section: Resultssupporting
confidence: 91%
“…It was recently suggested that Fos oncoproteins induce deregulation of genes encoding cytoskeleton-associated proteins (Jooss et al, 1995). We have previously observed down-regulation of tropomyosin 1-3 in breast carcinoma tissue (Franzen et al, 1996). In the present study, significant down-regulation was observed for tropomyosin 2 and 3.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to our findings, low expression of TM1 and TM2 has been detected in cervical carcinoma (Bae et al, 2005), of TM2 in oesophageal squamous cell carcinoma (Jazii et al, 2006) and of TM1 in breast carcinoma (Franzen et al, 1996;Raval et al, 2003). However, higher levels were found in primary breast cancer that had metastasised to the axillary lymph nodes (Franzen et al, 1996).…”
Section: Cytoskeletal Proteinssupporting
confidence: 78%
“…Clearly, literature has documented evidence of elevated expression of thymosin b4 (a G-actin-sequestering protein that inhibits actin polymerisation) and loss of tropomyosin (an F-actin-stabilizing protein) correlating with increased aggressiveness of carcinoma cells (Franzen et al, 1996;Kobayashi et al, 2002;Wang et al, 2004). In fast migrating tumour cells, a moderate decrease in cellular F-actin level can potentially enhance cell motility by either increasing the availability of G-actin for actintreadmilling, and/or decreasing the overall rigidity of cell cortex (enhances membrane deformability).…”
Section: Discussionmentioning
confidence: 99%